please ans this very urgent!!
![](https://hi-static.z-dn.net/files/d3c/25c3c589771f3c4eadabb2b489686f84.jpg)
Answers
Answer 99
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2 = 3+2-2√6 + 3+2+2√6
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2 = 3+2-2√6 + 3+2+2√6 3+2+2√6 3+2 -2√6
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2 = 3+2-2√6 + 3+2+2√6 3+2+2√6 3+2 -2√6 = 5 - 2√6 + 5 + 2√6
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2 = 3+2-2√6 + 3+2+2√6 3+2+2√6 3+2 -2√6 = 5 - 2√6 + 5 + 2√6 5 + 2√6 5 - 2√6
x^2 + y^2 = (√3-√2)^2 + (√3+√2)^2 (√3+√2)^2 (√3-√2)^2 = 3+2-2√6 + 3+2+2√6 3+2+2√6 3+2 -2√6 = 5 - 2√6 + 5 + 2√6 5 + 2√6 5 - 2√6 = 25 +24 -20√6 +25 +24+20√6
= 98 + xy
= 99
( xy will be 1)